The home and school environments, physical activity levels, and adiposity indices of school-age children - Patience K Gaa; Charles Apprey; Reginald Annan; Victor Mogre; Victoria P Dzogbefia (Intelektual Pustaka Media Utama, 2019)
The home and school environments as well as physical activity may be linked to the development of childhood obesity. We evaluated the home and school environments (HSEs), physical activity levels (PAL), television viewing (TVV) and their associations with adiposity indices of school-age children. This cross-sectional study included children aged 6-12 years and their parents from Tamale, Ghana. HSEs and TVV were assessed using questionnaires. The physical activity questionnaire for children (PAQ-C) was used to assess children’s PALs. Weight, height and waist circumferences were measured using standard tools. About 45% of children lived within a walking distance to parks or outdoor recreation centres. Majority of the parents considered their neighbourhoods to be safe for children to engage in physical activity. Only 27% of the schools had a food and nutrition policy, and more than 70% had a field for outdoor activities. Children watched TV for an average of 1.7 hours/day. Mean physical activity scores was 2.51. The school-age children had mean (SD) BMI-for-age z-scores was -0.23(1.47). Time spent watching TV or playing video games was associated with children’s BMI-for-age z-scores (β=0.48, p=0.043), BMI (β=2.28 p=0.005), and % body fat (β=3.80, p=0.005). Child’s level of activity was negatively associated with waist circumference (β =-0.65, p<0.001). Lack of nutrition policy in schools was common. TVV hours predisposed children to excess weight whiles physical activity decreased the likelihood of being obese.